2018
DOI: 10.1080/00913847.2018.1462651
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with self-reported injury history in female youth soccer players

Abstract: musculoskeletal injuries were associated with age, weight, and bmi in female youth players. the current study indicates that maintaining proper body composition may be beneficial to reduce musculoskeletal injuries among female youth soccer players.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 40 publications
1
27
1
Order By: Relevance
“…Of the 36 injured athletes, only 25.0% were not in the "healthy weight" category: 7 athletes were in the overweight category (BMI range 25 to 30 kg/m 2 ), 1 athlete was in the obese category (BMI 30 kg/m 2 or more), and one athlete was in the underweight category (BMI less than 18.5 kg/m 2 ). This finding of a higher BMI being associated with a greater risk of injury is consistent with prior studies [13,14,16]. A higher BMI (>21.5 kg/m 2 ) and lower total training time per week (<14.75 h/w) was also associated with a greater risk of LQ injury (RR = 3.1 (95% CI: 1.7, 5.5)).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Of the 36 injured athletes, only 25.0% were not in the "healthy weight" category: 7 athletes were in the overweight category (BMI range 25 to 30 kg/m 2 ), 1 athlete was in the obese category (BMI 30 kg/m 2 or more), and one athlete was in the underweight category (BMI less than 18.5 kg/m 2 ). This finding of a higher BMI being associated with a greater risk of injury is consistent with prior studies [13,14,16]. A higher BMI (>21.5 kg/m 2 ) and lower total training time per week (<14.75 h/w) was also associated with a greater risk of LQ injury (RR = 3.1 (95% CI: 1.7, 5.5)).…”
Section: Discussionsupporting
confidence: 89%
“…Another potential risk factor for musculoskeletal injury that warrants assessment in female collegiate soccer players is body mass index (BMI). Several studies have identified BMI as a risk factor for injury in soccer players [12][13][14][15][16]. A greater BMI was associated with a 1.43 times greater risk of injury in teenage female soccer players and a 1.51 times greater risk of lower extremity (LE) injury in elite female soccer players [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies conducted multivariate analyses to investigate the relationship between physical fitness and ‘any injury’ classification in female, team ball sport players. Four studies utilised a time-loss injury definition [ 62 , 78 , 100 , 104 ] and one study used a medical attention injury identifier [ 82 ]. One prospective study (level II) investigated total days injured from ‘any injury’ [ 104 ], whereas the remaining prospective studies (levels I and II) examined ‘any injury’ that occurred over one season [ 62 , 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…One prospective study (level II) investigated total days injured from ‘any injury’ [ 104 ], whereas the remaining prospective studies (levels I and II) examined ‘any injury’ that occurred over one season [ 62 , 78 ]. Two cross-sectional studies (level III) explored history of ‘any injury’ that occurred during sport [ 82 , 100 ]. Blokland and colleagues [ 62 ] also explored risk factors for any non-contact, recurrent, and match injury classifications.…”
Section: Resultsmentioning
confidence: 99%